Preventing Postpartum Breast Engorgement: Cabbage Leaf Compresses vs. Marmet Technique - Hadriani Hadriani; Niluh Nita Silfia; Hastuti Usman; Yuli Admasari; Masita Rahmadani (Jurnal Bidan Cerdas, 2025)
Background: one of the common problems associated with breastfeeding and exclusive breastfeeding is breast engorgement until the incidence rate reaches 20%-70% in nursing mothers. Engorgement of the breasts can be prevented non-pharmacologically, namely by compressing cold cabbage leaves and the marmet technique. The study aimed to compare the effectiveness of cold cabbage leaf compresses and the Marmet technique in preventing postpartum breast engorgement in normal puerperal mothers. Methods: Types of pre-experimental research with One-shot case study design namely cabbage compress (duration 30 minutes) and marmet technique given 1 time. The total sample of 30 respondents, was divided by 15 respondents in each group and sampling by non-probability sampling type of consecutive sampling. The measuring instrument uses an observation sheet containing a six-point engorgement scale (SPES). Data was analyzed using the Wilcoxon and Mann-Whitney test (p<0,05). Results: analysis of the effect of cold cabbage leaf compress management and marmet technique on the prevention of breast engorgement for normal puerperal mothers was obtained in cold cabbage leaf compresses p-value of 0.014 and in the marmet technique obtained p-value 0.317. The results of the analysis of the effectiveness of the two techniques were obtained with a p-value of 0.007 or <0.05. Conclusion: Cold cabbage leaf compresses were significantly more effective in reducing breast engorgement compared to the Marmet technique in the Independent Practice of Midwives (PBM) Setia of Palu City. It is recommended to use both techniques in helping to prevent breast engorgement for normal puerperal mothers.